Flagellum Is Responsible for Promoting Effects of Viable Escherichia coli on Calcium Oxalate Crystallization, Crystal Growth, and Crystal Aggregation - Kanlaya, Rattiyaporn; Naruepantawart, Orapan; Thongboonkerd, Visith (Frontiers in Microbiology, 2019)
Urease-producing bacteria (especially Proteus mirabilis) can cause infection kidney stone. However, recent studies have shown that intact viable non-urease-producing bacteria such as Escherichia coli might also promote calcium oxalate (CaOx) kidney stone formation but with unclear mechanism. We thus hypothesized that some relevant bacterial components might be responsible for such promoting effects of the intact viable E. coli. Flagella, capsule, lipopolysaccharide (LPS), and outer membrane vesicles (OMVs) were isolated/purified and their stone modulatory activities were evaluated using CaOx crystallization, crystal growth, and crystal aggregation assays. Among these, flagella had the most potent promoting effects on CaOx crystallization, crystal growth, and crystal aggregation. Validation was performed by deflagellation demonstrating that the deflagellated intact viable E. coli had markedly reduced CaOx crystal modulatory activities in all aspects (comparable to those of the negative controls). Similarly, neutralization of the isolated/purified flagella using a specific anti-flagellin antibody, not an isotype control, could abolish the promoting effects of flagella. These findings provide direct evidence indicating that flagellum is responsible for the promoting effects of the viable E. coli on CaOx crystallization, crystal growth and aggregation.